The effect of teaching design in accordance with cluster thinking strategies on First-grade-intermediate students’ achievement in science (Journal Of Educational and Psychological Researches, 2018)
The current study aims to develop a teaching design in accordance with cluster thinking strategies and explore the effect of this teaching design on students’ achievement in science. To this end, the null hypothesis was adopted: there is no statistically significant difference at the level of (0, 05) between experimental group who adopted the teaching design in learning science and control group who follow the traditional method in learning the same subject. To test the null hypothesis, total of (74) students from Al-Alaama Hussain Mahfooth intermediate school were selected intentionally for the academic year 2016-2017. The sample divided into two equal groups when all the variables (age, prior achievement of science, and prior knowledge of students) have been examined. The researcher prepared (142) lessons divided equally, (71) plans for each group. These lessons were exposed to group of experts specialized in teaching methods, educational psychology, and measurement and evaluation to scrutinize lessons’ validity and reliability. To collect the needed data, a questionnaire of (50) items, four likert points, were administered to the sample of study. The findings of study revealed that experimental group showed a highly significant difference comparing to the control group, based on this result, the researcher recommended to rethink of the methods of teaching and the educational programs in colleges of education, and  to focus on these designs that positively effect on students achievement and developing their high thinking skills.